EFFECT ANALYSIS OF COMPENSATION, WORK ENVIRONMENT AND LEADERSHIP ON SHIP CREW LOYALTY WITH WORK MOTIVATION AS INTERVENING VARIABLE AT PT. SALAM PACIFIC INDONESIA LINES - Budiyono, Budiyono; Tri Widyastuti; Muhammad Richo Rianto (Dinasti International Journal of Management Science, 2022)
The research aims to measure the effect of compensation, work environment and leadership on ship crew loyalty with motivation as an intervening variable at PT. Salam Pacific Indonesia Lines. This research is a quantitative research in which the object used is the ship's crew in the engine room. The number of samples used as many as 53 respondents. The design used is hypothesis testing using the structural equation model (SEM) – Smart PLS version 3.3.3. The results of this study indicate that compensation, leadership and motivation have a significant effect on ship crew loyalty. However, there is no evidence that the work environment effects the loyalty of ship crews. This study also shows that there is an indirect effect of compensation on ship crew loyalty through motivation, there is an indirect effect of leadership on ship crew loyalty through motivation, but there is no evidence of an indirect effect of work environment compensation on ship crew loyalty